Expression quantitative trait analysis reveals fine germline transcript regulation in mouse lung tumors. Issue 2 (1st June 2016) - Cotroneo, Chiara E.; Dassano, Alice; Colombo, Francesca; Pettinicchio, Angela; Lecis, Daniele; Dugo, Matteo; De Cecco, Loris; Dragani, Tommaso A.; Manenti, Giacomo
Highlights: Gene expression modulates cellular functions in tumors. Pas1 locus is the major modulator of lung tumorigenesis in mice. Pas1 acts as a major regulator of transcription in lung tumors. Components or targets of the Ras–Erk and Pi3k–Akt signaling pathways are involved. Abstract: Gene expression modulates cellular functions in both physiologic and pathologic conditions. Herein, we carried out a genetic linkage study on the transcriptome of lung tumors induced by urethane in an (A/J x C57BL/6)F4 intercross population, whose individual lung tumor multiplicity (Nlung) is linked to the genotype at the Pulmonary adenoma susceptibility 1 ( Pas1 ) locus. We found that expression levels of 1179 and 1579 genes are modulated by an expression quantitative trait locus (eQTL) in cis and in trans, respectively (LOD score > 5). Of note, the genomic area surrounding and including the Pas1 locus regulated 14 genes in cis and 857 genes in trans . In lung tumors of the same (A/J x C57BL/6)F4 mice, we found 1124 genes whose transcript levels associated with Nlung (FDR < 0.001). The expression levels of about a third of these genes (n = 401) were regulated by the genotype at the Pas1 locus. Pathway analysis of the sets of genes associated with Nlung and regulated by Pas1 revealed a set of 14 recurrently represented genes that are components or targets of the Ras–Erk and Pi3k–Akt signaling pathways. Altogether our results illustrate the architecture of germline control of gene expression in mouse lung cancer: they highlight the importance of Pas1 as a tumor-modifier locus, attribute to it a novel role as a major regulator of transcription in lung tumor nodules and strengthen the candidacy of the Kras gene as the effector of this locus.